Inadaptación escolar en alumnos de 6° grado de instituciones educativas diferenciadas del Callao - Melgar Cuadros, Giovanna María (2012)
This investigation is descriptive - comparative where the intention of that was to know the disadjustment - school to adapt in its different dimensions in students of 6th grade of educational institutions differentiated from Callao. We applied the Test to himself evaluation with Multifactorial of Adjustment - Failure to adapt TAMAI II (Hernández, P. 1993). The sample consisted of students in the 6th grade with ages between 11 and 12 years, 100 of which belong to an educational center of the armed forces and 130 belong to an educational state center. The results show that significant differences do not exist in the levels of adjustment - school failure to adapt between both institutions, nevertheless with regard to his dimensions if We found significant differences in the dimension of distaste to the teacher. Being the percentages higher in the educational center of the armed forces.